M2M system for efficient water consumption in sanitary services, based on intelligent environment (2018)
This paper describes the fulfilled research process for the development of an intelligent system for the efficient use of water in sanitary units in the domestic environment. Fundamentally, the research focused on two processes, firstly, the development of a high reliability system to monitor the actual consumption of sanitary units and secondly the development of an enhanced system for the intelligent control of consumption of the same sanitary unit. The research highlights the constitution of an M2M technological solution, with high precision that impacts environmental sustainability, through the generation of awareness regarding the rational use of water resources in daily actions of personal hygiene.